The Effect of Workload, Work shift and Work duration to Work Fatigue of Inpatient Nurses at Gambiran Hospital Kediri City - Erlando Syaiful Khaqim; Indasah; Novita Ana Anggraini (Ficco Public Health Journal, 2025)
Background: Fatigue is a common problem in both formal and informal workplaces. World Health Organization (WHO) states that mental disorders in workers such as feelings of excessive fatigue lead to depression and are the second most common disease after heart disease. Work fatigue is a common problem in the workplace that is often encountered in the workforce and is a problem that requires attention. This study aims to Analyze the influence of workload, work shifts and work duration to work fatigue of inpatient nurses at Gambiran Regional Hospital, Kediri City. Methods: This research is quantitative with cross-sectional design, population in this research were all inpatient nurses total 174 nurses at Gambiran Hospital Kediri City. Based on slovin formula, sample in this research was 103 respondents. Data collection using questionnaire distributed directly to inpatient nurse, then analysis using multiple linier regression. Results: The regression analysis shows that workload and work duration significantly affect work fatigue among inpatient nurses at Gambiran Hospital, while work shifts do not. Work duration has the greatest influence, indicating that longer working hours increase fatigue more than workload. These findings align with previous studies showing that heavy workload and prolonged working hours contribute to nurse fatigue, whereas well-managed shift systems may mitigate its impact. Conclusions: The regression test results show that work duration has the greatest influence followed by workload, suggesting the need for further research on work fatigue with different variables among nurses in the Emergency Installation Room or Intensive Care Unit.